The Role of Islam in Indonesia and AlgerianHistory: A Comparative Analysis - Meuleman, J.H. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1994)
In this article the authors propose a comparative note on the role of Islam in the history of the two countries: Algeria in the Maghreb region and Indonesia on the southeast end of the region of the spread of Islam. The author explains that in various periods, Islam plays a very important role in the history of the two countries. Period covered specifically is the eve of the arrival of Islam - which is described to explain the circumstances behind the arrival of the new religion - and then the process of Islamization, Islamic role in the resistance against the occupation, and finally the position of Islam in the post-colonial independent state.DOI: 10.15408/sdi.v1i2.856